(3TQM CHjGJ Gdedhj aj GdCTcGd GdCQHYIs - (3GdMdHj, EHQGgje Hf eMeO EHQGgje, J (B956 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG Edi SHjd GdQTGO deG QCjJ GdCHjGJ GdKdGKI dTjNfG Gdedhj eONdI fGaYI aj GSJMVGQ VQhH GdCTcGd GdCQHYI eQJHI HGdJQJjH GdWHjYj hgj bhdg s
(3BNQgG (B:s
(3GdSGOS GdGSJbQGA hgh Gf ojLQi GdVQH aj LejY GMJeGdGJ GNJdGW eGOI UaQGA hcHQGg aEf UOjb aj LejYgG agh efJgL hEf cPH aj HYgVG agh ZjQ WQO GdGfJGL ajchf YbjeG JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdQjGVjGJs